Advantages and Limitations of EHR Use in Clinical Workflows - Magnusson,Alma; Hall Andreasson,Ebba (2025)
Electronic Health Record (EHR) systems are central to modern healthcare, yet their practical impact on clinical workflows remains complex. This thesis explores the advantages and limitations physicians experience when using EHR systems in daily hospital work. Guided by the Systems Engineering Initiative for Patient Safety (SEIPS) framework, the study takes a socio-technical approach, focusing on how technology, tasks, users, and organizational conditions interact to shape system use. Semi-structured interviews were conducted with physicians at a Swedish university hospital, and thematic analysis was used to identify key patterns. Findings show that while EHR systems improve access to patient data and support clinical decision-making, challenges related to poor interface design, fragmented systems, and insufficient training continue to hinder workflow efficiency. These issues are not isolated but interconnected across SEIPS dimensions, reflecting broader misalignments between system design and clinical reality. The study contributes to the field of Information Systems by offering context-rich insights into how EHRs are experienced in practice and highlighting the value of sociotechnical perspectives in evaluating digital health tools.
Keywords: Electronic Health Records (EHR); Clinical Workflow; Physician Experience; SEIPS Framework; Sociotechnical Systems